2013
DOI: 10.1183/09031936.00071812
|View full text |Cite
|
Sign up to set email alerts
|

Automated quantification of radiological patterns predicts survival in idiopathic pulmonary fibrosis

Abstract: Accurate assessment of prognosis in idiopathic pulmonary fibrosis remains elusive due to significant individual radiological and physiological variability. We hypothesised that short-term radiological changes may be predictive of survival.We explored the use of CALIPER (Computer-Aided Lung Informatics for Pathology Evaluation and Rating), a novel software tool developed by the Biomedical Imaging Resource Laboratory at the Mayo Clinic Rochester (Rochester, MN, USA) for the analysis and quantification of parench… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
139
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(149 citation statements)
references
References 29 publications
3
139
1
3
Order By: Relevance
“…Future studies should also consider whether sLOXL2, along with other promising prognostic IPF biomarkers (e.g. matrix metalloproteinase (MMP)1, MMP7, KL-6, periostin, surfactant protein-A and D, CC chemokine ligand 18, vascular endothelial growth factor and YKL-40) [19][20][21][22][23][24][25][26][27][28][29], as well as prognostic scores [30,31] and radiological modalities [32], might have prognostic value for helping physicians and patients anticipate the patient's IPF disease progression. This might include evaluation of serially collected sLOXL2 levels and their relationship to IPF acute exacerbations, which represent a terminal event for many IPF patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should also consider whether sLOXL2, along with other promising prognostic IPF biomarkers (e.g. matrix metalloproteinase (MMP)1, MMP7, KL-6, periostin, surfactant protein-A and D, CC chemokine ligand 18, vascular endothelial growth factor and YKL-40) [19][20][21][22][23][24][25][26][27][28][29], as well as prognostic scores [30,31] and radiological modalities [32], might have prognostic value for helping physicians and patients anticipate the patient's IPF disease progression. This might include evaluation of serially collected sLOXL2 levels and their relationship to IPF acute exacerbations, which represent a terminal event for many IPF patients [33].…”
Section: Discussionmentioning
confidence: 99%
“…A machine-learning algorithm is then used to develop a predictive model for specific CT patterns [46]. MALDONADO et al [73] used a novel computer-aided system called CALIPER to quantify fibrosis in IPF based on unique HRCT texture patterns for ground-glass opacification, honeycombing and reticulation. The authors evaluated changes in those HRCT-derived patterns between two time points (3-15 months apart) and showed that changes in reticulation and total fibrosis were predictive of survival.…”
Section: Quantitative Computed Tomographymentioning
confidence: 99%
“…In addition, to date, it has primarily focused on evaluating the extent of parenchymal abnormalities as a surrogate for fibrosis severity, with less emphasis on other variables such as lung volumes [73,74] or the degree of traction bronchiectasis. The issue of CT protocol standardisation is nevertheless equally important, if not more so, for automated evaluation.…”
Section: Strengths and Limitations Of Ct In Staging Of Ipfmentioning
confidence: 99%
“…Several studies have identified independent predictors of mortality in patients with IPF, including age, respiratory hospitalisation, forced vital capacity (FVC) % predicted, and longitudinal change in FVC % pred [5][6][7][8][9][10][11][12][13][14][15][16]. The 6-min walk distance (6MWD), a practical and widely used measure of clinical status in patients with a variety of cardiopulmonary diseases [17][18][19][20][21][22], has recently been shown to be associated with the risk of mortality in patients with IPF [23][24][25]; however, the independent contribution of 6MWD to the risk of mortality has not been formally evaluated in a large, well-defined population of patients with IPF.…”
Section: Introductionmentioning
confidence: 99%